2014
DOI: 10.1177/0013164414559071
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Classical Test Theory and Item Response Theory Frameworks via Factor Analytic Models

Abstract: There are well-defined theoretical differences between the classical test theory (CTT) and item response theory (IRT) frameworks. It is understood that in the CTT framework, person and item statistics are test- and sample-dependent. This is not the perception with IRT. For this reason, the IRT framework is considered to be theoretically superior to the CTT framework for the purpose of estimating person and item parameters. In previous simulation studies, IRT models were used both as generating and as fitting m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 26 publications
1
28
0
3
Order By: Relevance
“…These relationships can be seen as closely tied to those between factor analysis (FA) and IRT, which have been pointed out in the methodological literature over the past 30 years or so (e.g., Kamata & Bauer, 2008;B. O. Muthén, Kao, & Burstein, 1991;Takane & de Leeuw, 1987; see also Kohli, Koran, & Henn, 2014). The CTT-IRT relationships, when appropriately highlighted and methodically clarified for empirical educational, behavioral, and social researchers, can in our view significantly contribute to improvements in their measurement related work as well as to tangible progress in the entire field of measurement.…”
mentioning
confidence: 83%
“…These relationships can be seen as closely tied to those between factor analysis (FA) and IRT, which have been pointed out in the methodological literature over the past 30 years or so (e.g., Kamata & Bauer, 2008;B. O. Muthén, Kao, & Burstein, 1991;Takane & de Leeuw, 1987; see also Kohli, Koran, & Henn, 2014). The CTT-IRT relationships, when appropriately highlighted and methodically clarified for empirical educational, behavioral, and social researchers, can in our view significantly contribute to improvements in their measurement related work as well as to tangible progress in the entire field of measurement.…”
mentioning
confidence: 83%
“…Unlike factor analysis, however, IRT assumes nominal or ordinal indicator variables, which entails different modeling and estimation methods. Although several researchers have shown that CTT and IRT often produce similar conclusions concerning the psychometric properties of measures (e.g., Kohli, Koran, & Henn, ; Raykov & Marcoulides, ), it is useful to conduct IRT because its results provide a distinct way of evaluating the psychometric properties of scales and their component items, and can demonstrate robustness of results obtained using CTT methods.…”
Section: Introductionmentioning
confidence: 99%
“…However, when skewed items were analyzed, the θ often outperformed the sum score. Various other studies compared the θ‐values with the corresponding sum score from real data as well as from simulated data and found similar minor differences. In an example using real data, various tests of extraversion and neuroticism were summarized via θ‐values and sum scores; the median correlations were r = .96.…”
Section: Discussionmentioning
confidence: 65%